Electrically Activated Paper Actuators. (17th February 2016) - Hamedi, Mahiar M.; Campbell, Victoria E.; Rothemund, Philipp; Güder, Firat; Christodouleas, Dionysios C.; Bloch, Jean‐Francis; Whitesides, George M.
Abstract : This paper describes the design and fabrication of electrically controlled paper actuators that operate based on the dimensional changes that occur in paper when the moisture absorbed on the surface of the cellulose fibers changes. These actuators are called "Hygroexpansive Electrothermal Paper Actuators" (HEPAs). The actuators are made from paper, conducting polymer, and adhesive tape. They are lightweight, inexpensive, and can be fabricated using simple printing techniques. The central element of the HEPAs is a porous conducting path (used to provide electrothermal heating) that changes the moisture content of the paper and causes actuation. This conducting path is made by embedding a conducting polymer (PEDOT:PSS) within the paper, and thus making a paper/polymer composite that retains the porosity and hydrophilicity of paper. Different types of HEPAs (straight, precurved, and creased) achieved different types of motions (e.g., bending motion, accordion type motion). A theoretical model for their behavior is proposed. These actuators have been used for the manipulation of liquids and for the fabrication of an optical shutter. Abstract : Hygroexpansive electrothermal paper actuators (HEPAs) are fabricated from paper, conducting polymer and adhesive tape, and operate based on the moisture‐induced dimensional changes of paper. The central element of the HEPAs is a porous conducting path (used to provide electrothermal heating). A theoretical model for their behavior is proposed. These actuators can be used for the manipulation of liquids and for the fabrication of an optical shutter.